EKSISTENSI KONSEP DISKRESI SEBAGAI SARANA PEMBAHARUAN MASYARAKAT DALAM PENEGAKAN SUPREMASI HUKUM - Fahmy Asyhari Asyhari (PIKTORIAL : Journal of Humanities, 2019)
ABSTRACT Reforms that occured in Indonesia at this time showed an excessive state,meaning that each individual community to implement reforms violence. This condition we see from various print and electronic mass media which describes the brutality and as if there is no law enforcement. This situation raises a question about the existence of the law itself, is still a commander or even the law into something it’s just rhetoric. The emergence of public mistrust of law and law enforcement is a form of public mistrust of government authority. Associated with the authority of government because the government has the authority or power to direct the public, and responsible for serving the public interest. Law and public policy (discretion) is the policy of the government are identical interlinked with each other. Application of the law is in need of public policy to actualize the law in society.Similarly, a public policy implementation in law enforcement may not run properly if its implementation is not based on the fundamentals of a strong legislation. This is the reason for the origin of a lack of respect for the law is that the law is not created from the legal joints are living in the community, so that people obey the law then the law should be made according to the rules/laws are living in the midst of society, and the subsequent legal formed it into a means of renewal communities to uphold the rule of law. Keywords : The concept of discretion, community, the enforcement of law supremacy